Methodology to Produce Hard Coherent Water Adsorbent Using Modified Fusion Method - A .A., Azharin Shah; Nour, A. H.; R. M., Yunus (AENSI Publishing, 2014)
Efforts were given to find suitable method to produce hard and coherent water adsorbent for ethanol water mixture. Three methods were studied. In the first method, calcined clay was mixed with alumina and KOH or NaOH. Water was added to get 40-50% solution and thoroughly mixed. The mixture was aged for 48 hours in closed container at 38oC followed by crystallization. In the second method, calcined clay or pure silica and alumina sources were mixed with NaOH or KOH and fused in furnace at 550oC for 12 hours. The fused mixture was mixed with water to get 40-55% solution of KOH or NaOH. Aging was carried out at 38oC for 48 hours before crystallization took place. In the third method, fused mixture from method 2 was mixed with NaOH or KOH and 5 part of water. The mixture was vigorously stirred for 3 hours and left for aging/crystallization at 60oC for 24 hours in oven. All the products from the three methodologies were washed and dried before being tested for water adsorbance. Results showed that method 2 was able to produce water adsorbent. The experimental results also revealed that the repetition of reflux may improve the water adsorbance performance of the adsorbent. However XRD analysis showed that the product was not the type of zeolite A.